2012
DOI: 10.9734/bjemt/2012/1284
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Risk Status of Small Scale Farmers in Niger State, Nigeria

Abstract: Aims: To ascertain the risk status of farming households and whether the risk status is accentuated by some factors. The specific objective is to determine the relationship between their risk status and socio-economic characteristics and food security status in the study area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…It therefore means that the model is capable of showing and explaining the determinants of level of awareness of the respondents. This indication is also confirmed by the LRI of respondents, amount spent on purchase (+), farm size (+) and 0.5533 which is quite higher than that obtained by Nmadu et al [17], Rahji and Fakayode [19], Abadi ghadim and Pannell, [20] and Zepeda [21]. The model further shows that while number of years spent in formal education (+) and educational age (-) also determined the probability of high level of awareness significantly.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It therefore means that the model is capable of showing and explaining the determinants of level of awareness of the respondents. This indication is also confirmed by the LRI of respondents, amount spent on purchase (+), farm size (+) and 0.5533 which is quite higher than that obtained by Nmadu et al [17], Rahji and Fakayode [19], Abadi ghadim and Pannell, [20] and Zepeda [21]. The model further shows that while number of years spent in formal education (+) and educational age (-) also determined the probability of high level of awareness significantly.…”
Section: Resultssupporting
confidence: 71%
“…The final estimates were selected based on the variables that converged during iteration. The coefficients of the base outcome were then recovered in line with in line with Nmadu et al [17] …”
Section: Methodsmentioning
confidence: 56%
“…The level of education contributes much for productivity, adoption of new technology and farming techniques. This agrees with the findings of Okoruwa et al (2002 ) and Nmadu, et al, (2012). Tables 1 revealed that The result in Table: 2 show the sources of risks experienced by the farmers in rice post harvest management.…”
Section: Resultssupporting
confidence: 91%
“…Hao (2010) elaborated on the fact that there are great differences among the three types of risk-behaviour categories in farmer's supply response. Nmadu et al (2012), indicated that farmers' risk attitudes are major determinants of the rate of diffusion of new technologies among them and the outcome of rural development programs. They further noted with reference from (Adebusuyi, 2004;Alderman, 2008) that risks cause farmers to be less willing to undertake activities and investments that have higher expected outcomes but carry with them high risk of failure…”
Section: Risky Behaviour and Its Impacts On Agricultural Decision Makingmentioning
confidence: 99%
“…A risk attitudinal scale with a set of questions relevant to farmers' farm-related decisions was used to identify the risk status of the farmers. This method of measuring the risk aversion of the farmers was adapted from Nmadu et al (2012) who presented a set of ten questions to the farmers which were related to their risk seeking behaviour. Following from that and applying to this study, each farmer was made to choose his response to the questions from five (5) indicating strongly disagree to one (1) indicating strongly agree.…”
Section: Identification Of Risk Statusmentioning
confidence: 99%